TikTok, educación y aprendizaje - Sánchez Rogel, María Guissella (2024)
TikTok, a social media platform that has gained appeal among today's youth because to its quick growth, is now regarded as an educational tool. Its prolonged use covers students from “Ramón Samaniego Palacios” high school in the El Arenal parish, Puyango canton, Loja province. The goal of the research is to create a campaign for education and awareness on the use of the TikTok social network as a learning tool for high school students in the "Ramón Samaniego Palacios" Educational Unit. Apart from this goal, determining the impact of TikTok on high school pupils was suggested. The study begins with a documentary review, mixed methodology (qualitative – quantitative) with interviews applied to teachers, educational authorities, as well as surveys to 30 parents and 47 high school students; two focus groups and the participant observation of the researcher in the educational environment. The factors included the amount of time spent using the platform, the activity within it, the opinions of parents, instructors, and students, as well as support for the campaign. Although TikTok can be a useful teaching tool, not everyone is aware of all of its benefits. The situation gets worse when 91.49% of time is spent on entertainment, although the campaign is well-received. In conclusion, it is possible to implement a training and awareness campaign on the use of TikTok as an educational instrument, which may help people use the social network in a constructive and pedagogical way. Key words – TikTok, education - learning, educational tool, students, training campaign.